Diffusing student performance in using blended learning models in higher learning - Mukhithi, Avrill; Phahlane, Mampilo; Malungana, Lario (Frontiers in Education, 2025)
BackgroundGlobal education systems underwent a dramatic transformation due to the COVID-19 pandemic, forcing a sudden shift to online and hybrid learning methods. Understanding the long-term impacts of blended learning on student performance and engagement is still essential as educational institutions work through the post-pandemic recovery in countries such as South Africa.ObjectivesThe study aims to assess the degree of integration of blended learning into higher education institutions (HEIs) in South Africa post pandemic.MethodsThe study used a systematic literature review (SLR) method, consulting a wide variety of academic publications from Sabinet, Springer, Emerald, Science Direct and Google Scholar, to conduct a critical analysis of blended learning approaches in higher education in South Africa.ResultsResults indicate that addressing structural deficiencies in training, infrastructure, and institutional support is necessary for successful implementation to ensure equitable access, participation, and improve student performance.ConclusionThe research paper shows how blended learning significantly affects student performance, yielding mixed findings; some report that flexibility and participation lead to better results, while others highlight issues with self-regulation and unequal access to resources. For blended learning to reach its full transformative potential, South African institutions must prioritize comprehensive faculty training, equitable digital access, and targeted support systems that bridge pedagogical and technological gaps, thus creating inclusive and stimulating learning environments for all students.